Processo Penal Garantista e Repressão ao Crime Organizado - a legitimidade constitucional dos novos meios operacionais de investigação e prova diante do princípio da proporcionalidade - Pimentel, José Eduardo de Souza (2006)
Criminal procedure has two functions, which are equally relevant in the Democratic State under the Rule of Law. The first one, is to ensure the dignity of those accused determining that, to exercise its right to punish [jus puniendi], the State must conduct its actions based on the full respect for the rights of the individual. The second one, is to meet the social interest that the purpose of criminal procedure be the full and accurate enforcement of the law in order to accomplish the mission of securing peace and order in society. The identification of organized crime and rising violent crime rates among us have contributed for the creation of specific laws in the field of Brazilian criminal procedure, thus adding new operational means of investigation and proof in order to improve effectiveness. Such criminal instruments are highly incisive and endanger the rights of the individual and the procedural principles. In view of this new social and regulatory scenario, the constitutional legitimacy of these mechanisms is analyzed in the light of the principle of reasonability. It is finally suggested that the protective purpose of criminal procedure be sought, as closely as possible, by reasserting the accusation pattern and redefining the roles of the criminal judge and the Ministério Público [the Public Prosecutor s Office ], with emphasis on the investigation.